Interrelationship between environmental degradation, geopolitical risk, crude oil prices, and green bonds: Evidence from the globe by sectoral analysis - Kartal, Mustafa Tevfik; Taskin, Dilvin; Depren, Serpil Kilic (ELSEVIER, 2024)
By considering the motion of the world is our home, this study investigates the interrelationship between environmental degradation, geopolitical risk, crude oil prices, and green bonds across the globe. So, the research considers the probable differences between the sectors by making a detailed analysis of CO 2 emissions across sectors, applies the novel WLMC method, and uses daily data from 2nd January 2020 through 30th November 2023 for a time and frequency -based empirical analysis. The outcomes present that (i) the geopolitical risk is the most important variable on CO 2 emissions between 2020/1 and 2021/11 followed by Brent oil prices for the period 2021/12-2023/10; (ii) green bonds are highly effective on CO 2 emissions only around 2023/11; (iii) the impacts of the variables are quite weaker (stronger) at lower (higher) frequencies; (iv) the impacts of the variables are the same at aggregated and disaggregated levels; (v) the impact of the variables on CO 2 emissions change based on times and frequencies. Thus, the outcomes demonstrate new insights for differentiating impacts across times and frequencies, whereas the direction of the impacts is the same across aggregated and disaggregated levels. (c) 2024 International Association for Gondwana Research. Published by Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Sectoral Emissions; Geopolitical Risk; Crude Oil Prices; Green Bonds; The World; ECONOMIC-GROWTH; ENERGY; EMISSIONS; Geology